Posterior calcaneal spur length and angle are predictors of pain and functional limitation in insertional Achilles tendinopathy - Dinç, Mustafa; Soydemir, Ömer Cevdet; Karasu, Recep; Aykaç, Bilal; Bayrak, Hünkar Çağdaş (The European Research Journal, 2025)
Objectives: This study aimed to quantitatively evaluate the clinical impact of posterior calcaneal spur (PoCS) morphology, specifically spur length and inclination angle, in patients with insertional Achilles tendinopathy (IAT). Methods: This retrospective study analyzed 200 patients with symptomatic IAT who underwent standardized weight-bearing lateral ankle radiographs. Spur length and inclination angle were measured, and patients were stratified into nine subgroups based on three length categories (10 mm) and three angle categories (20°). Clinical outcomes were assessed using the Visual Analog Scale (VAS), American Orthopaedic Foot and Ankle Society (AOFAS) score, and Victorian Institute of Sport Assessment-Achilles (VISA-A) score. Kruskal-Wallis tests and multivariate linear regression analyses were used to evaluate associations between spur morphology and outcomes. Results: Both longer spurs (>10 mm) and steeper inclination angles (>20°) were significantly associated with worse clinical scores including higher VAS scores and lower AOFAS and VISA-A scores (P10 mm and angles >20° had a mean VAS score of 7.22±0.65, VISA-A score of 49.72±2.54, and AOFAS score of 60.00±4.24, indicating greater pain and functional limitation. In contrast, patients with spur lengths